Konieczność ponownego wyrażenia zgody małżeńskiej w przypadku aplikacji uważnienia zwykłego małżeństwa z racji wystapienia przeszkody zrywającej - Dzierżon, Ginter (Ius Matrimoniale, 2010)
The author in the present article focused on a very specific problem of the need the renewal of marriage vows in the case of annulment caused by an annulling obstacle The main aim of the author was to present the legal arguments resulting from the disposition included in canon 1156 § 2. According to the analyses carried out, the legislator introduced this solution in order to strongly object to the validation of marriage on the strength of the law alone. Moreover, the author believes that the necessity for marriage vows renewal was introduced with a view to calming the conscience of the parties involved.